Multi-parasite infection in an immigrant from Ghana: potential for new epidemic foci - Maura Fiamma; Silvia S Longoni; Emmanuel E Siddig; Sonia Attene; Vito Astone; Antonio Nicoletti; Bianca Paglietti; Antonella Santona; Angela Fele; Riccardo Ivaldi; Francesco Logias (Journal of Infection in Developing Countries)
Introduction: Imported parasitosis, which do not require an invertebrate vector, are extremely dangerous and can lead to the occurrence of disease in currently parasite free areas. In the present study we report a case of multi-parasitic infection in a young immigrant from Ghana to Italy caused by filaria, Schistosoma sp. and Strongyloides sp.